2014
DOI: 10.1055/s-0034-1384939
|View full text |Cite
|
Sign up to set email alerts
|

A Comparison of the Diagnostic Accuracy and Reliability of Subjective Grading and Computer-Aided Assessment of Intranodal Vascularity in Differentiating Metastatic and Reactive Cervical Lymphadenopathy

Abstract: In the assessment of the degree of intranodal vascularity, the QCA method was more accurate and reliable than the QSG method in distinguishing metastatic and reactive lymph nodes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
(9 reference statements)
0
5
0
Order By: Relevance
“…Variable results for qualitative vascularity assessment can be attributed to the subjective grading of vascularity which is prone to interpreter bias. Quantitative vascularity analysis approaches based on segmentation of peripheral and central vascularity overcome limitations of subjective visual assessment of vascularity pattern and distribution [15,16,77]. Only one study demonstrated that the combination of Doppler ultrasound CAD with qualitative grey scale ultrasound features can result in an optimal sensitivity and specificity, but with reduced sensitivity compared to individual assessment of both qualitative and Doppler CAD [66].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Variable results for qualitative vascularity assessment can be attributed to the subjective grading of vascularity which is prone to interpreter bias. Quantitative vascularity analysis approaches based on segmentation of peripheral and central vascularity overcome limitations of subjective visual assessment of vascularity pattern and distribution [15,16,77]. Only one study demonstrated that the combination of Doppler ultrasound CAD with qualitative grey scale ultrasound features can result in an optimal sensitivity and specificity, but with reduced sensitivity compared to individual assessment of both qualitative and Doppler CAD [66].…”
Section: Discussionmentioning
confidence: 99%
“…Computer-aided diagnosis (CAD) systems have emerged in past years as non-invasive approaches to complement radiologists’ interpretation and potentially overcome subjective interpretation limitations. CAD detection and diagnosis methods are based on machine learning approaches that use statistical and data mining algorithms, which rely on textural ultrasound features and quantitative regional segmentation of vascularity, to differentiate benign and malignant nodules [13,14,15,16]. CAD software can be embedded within the ultrasound unit or be used as an isolated program for offline image analysis.…”
Section: Introductionmentioning
confidence: 99%
“…Computer-aided diagnosis (CAD) has attracted great attention of researchers as a newly developed technique that has potential in enhancing radiologists' interpretation and overcoming subjective limitations. The CAD detection and diagnosis methods are based on machine learning approaches that extract features based on shape, texture, and statistical values, differentiating benign and malignant nodules (5)(6)(7).…”
Section: Introductionmentioning
confidence: 99%
“…A previous study assessed intranodal vascularity by subjective visual judgement and classified lymph nodes according to the abundance of intranodal vascularity (13). Another study evaluated the diagnostic performance of solely VI analysis of lymph node but without studied the diagnostic performance of combining VI analysis with conventional ultrasound assessment of lymph node (16). In the present study, we have investigated the added value of VI analysis on conventional ultrasound assessment to distinguish between metastatic and tuberculous cervical lymph nodes.…”
Section: Discussionmentioning
confidence: 99%